PENETAPAN NILAI LIMIT HAK TANGGUNGAN DIBAWAH HARGA WAJAR OLEH KREDITOR ATAU PENJUAL - Nasichin, Mohamad; Candra, Ade (Fakultas Hukum Universitas Gresik, 2020)
ABSTRACTIn the determination of the limit value of the object of the Mortgage by the seller or creditors, it results in many losses for the debtor, the creditor on the pretext of paying off the creditors' receivables determines the value of the collateral object value below the fair value, even often the seller sets the limit value with the debtor's debt value. In the case of a creditor auctioning an object of mortgage on his own power through a public auction of object of mortgage, if the debtor is default, he should still consider that the object of mortgage is the property of the debtor. Because the debtor is the mortgage provider and the creditor should still prioritize the value of respect for the property of others. In this study, it is emphasized that in the implementation of the guarantee auction of Mortgage Rights through a Public Auction, KPKNL has not been able to provide the right and balanced solution between debtors and creditors. Because, in the Regulation of the Minister of Finance concerning Instructions for auction implementation, it does not define the determination of the lowest limit and the flow of determining the auction which is required to sell at market price first and does not provide a limit value below the liquidation value, besides that in the PMK it does not give authority to auction officers. KPKNL to impose sanctions on non-payment applicants if there is a price request by selling below a reasonable limit. So that the auction results are considered not fulfilling the principle of justice for the owner of the Object of the Mortgage.Ãƒâ€šÃ‚Â Keywords: Mortgage Guarantee;Ãƒâ€šÃ‚Â Default Loan; Determination of Limit Value; Ãƒâ€šÃ‚Â Debtor Legal ProtectionÃƒâ€šÃ‚Â AbstrakDalam penetapan nilai limit Objek Hak Tanggungan oleh penjual atau kreditor banyak mengakibatkanÃƒâ€šÃ‚Â kerugian bagi debior, kreditor dengan dalih untuk melunasi piutang kreditorÃƒâ€šÃ‚Â menetapkan nilai objek jaminan hak tanggungan dibawah nilai yang waja, bahkan sering terjadi penjual menetapkan nilai limit dengan nilai hutang debitor.Ãƒâ€šÃ‚Â Dalam halnya kreditor melakukan lelang objek hak tanggungan atas kekuasan sendiri melalui pelelangan umum objek hak tanggungan apabila debitor cedera janji seharusnya tetap mempertimbangkan bahwa objek hak tanggungan tersebut merupakan milik debitor.Ãƒâ€šÃ‚Â Karena debitor sebagai pemberi hak tanggungan dan seharusnya kreditor tetap mengedepankan nilai penghormatan kepada milik orang lain. Dalam penelitian ini menggaris bawahi bahwaÃƒâ€šÃ‚Â dalam pelaksanaan lelang jaminan Hak Tanggungan melalui Pelelangan Umum yaitu KPKNL belum bisa memberikanÃƒâ€šÃ‚Â solusi yangÃƒâ€šÃ‚Â tepat dan seimbang atara debitor dan kreditor. Karena , didalam Peraturan Menteri Keuangan Tentang Petunjuk Pelaksanaan lelang tidak mendefinisika mengenai penetapan batas terendahÃƒâ€šÃ‚Â dan alur penentuan lelang yang di haruskan menjual dengan harga pasaar terlebih dahulu dan tidak memberikan nilai limit di bawah nilai likuidasi, selain itu di dalam PMK tidak memberikn kewenagan kepada petugas lelangÃƒâ€šÃ‚Â KPKNL untuk memberikan sanksi kepada pemohon lelanag apabila adanya permaian harga dengan menjual dibawah limit yang wajar. Sehingga hasil lelang dianggap tidak memnuhi asas keadilan bagi pemilik Objek Hak Tanggungan.Ãƒâ€šÃ‚Â Kata Kunci : Jaminan Hak Tanggungan; Kredit Bermasa Cedera Janji; Penetapan Nilai Limit; Perlindungn Hukum Debitor.